Truth and Certainty in Peter Auriol - Bolyard, Charles (Vivarium, 2015)
This paper investigates the nature of truth and certainty according to the French Franciscan theologian Peter Auriol (1280-1322). In the first section, I attempt to harmonize a few different sections of Auriol’s Scriptum on book i of the Sentences: the accounts of truth as conformity in question 2 of the Prologue and question 10 of distinction 2, and the account of truth as quiddity in question 3 of distinction 19. In the second section, I explore the notion of certainty in question 1 of the Prologue. Here, Auriol’s taxonomy of propositions is explained, and the difference between scientific certainty and the certitude of faith is outlined. God works in the background in the context of both truth and certainty, and the fact that our cognitive processes are generally trustworthy makes Auriol’s epistemological position into a species of reliabilism.